More small tools for sweet challenges: advances in microfluidic technologies for glycan analysis - Pinnock, Ferra; Carten, Juliana Debrito; Daniel, Susan (Frontiers in Lab on a Chip Technologies, 2024)
Carbohydrates, also known glycans, are ubiquitous in nature and exhibit a wide array of biological functions essential to life. Glycans often exist as conjugates of proteins or lipids and reside predominantly at the surface of cells, where their structure and composition are known to vary in a disease-dependent fashion. This observation has encouraged the development of tools for monitoring glycan patterns on individual molecules, cells, and tissues, to elucidate the links between glycosylation and disease for therapeutic and diagnostic applications. Over the past two decades, microfluidic technology has emerged as an advantageous tool for profiling the glycan content of biological systems. Miniaturizing carbohydrate analysis can circumvent several challenges commonly encountered with conventional-scale analytical techniques such as low throughput and poor detection sensitivity. The latter is often complicated by the low abundance of glycans in biological specimens and the complexity of carbohydrate structures, which often necessitates extensive concentration and purification of glycans to discern their structural features. We previously examined the application of microfluidics in the synthesis of carbohydrates in a recent paper (Pinnock et al., 2023). This review builds upon that discussion by delving into the application of microfluidics in the complementary field of carbohydrate analysis. Special attention is given to applications related to glycomics and the ways that microfluidics have enhanced the sensitivity, reproducibility, and throughput of carbohydrate identification and structural characterization.